Influence of environmental factors and sessile biota on vagile epibionts: The case of amphipods in marinas across a regional scale - SAENZ-ARIAS, PABLO; NAVARRO-BARRANCO, CARLOS; GUERRA-GARCÍA, JOSÉ MANUEL (Mediterranean Marine Science, 2022)
Marinas are highly anthropized environments, with singular ecological characteristics. In the present study the spatial variability of the amphipod assemblage associated to floating pontoons was analyzed. Moreover, the influence of the environmental data and the sessile biota on the amphipod assemblage structure were assessed. Six marinas were selected along the Southern Iberian Peninsula, three in the Atlantic and three in the Mediterranean, and three floating pontoons were sampled at each marina. Four-teen amphipod species were identified, most of them corresponded to detritivores and generalist species. Statistical analyses considering amphipod composition and abundance did not show significant differences between the Atlantic and the Mediterranean, but there were significant differences among marinas. Copper had a significant correlation with the amphipod assemblage. The sessile species Bugula neritina and Ellisolandia elongata also showed a significant influence on the spatial patterns of the amphipod assemblages. Therefore, environmental conditions and sessile composition seem to affect, simultaneously, the spatial variability of amphipod assemblage associated to floating pontoons in marinas. Both factors are key to understand the singularity of marinas. This fact should be taken into consideration to prevent the use of a single management program in these environments.